Does Participation Lead to Ongoing Infrastructure Maintenance? Evidence from Caribbean Landslide Mitigation Projects - Holcombe, Elizabeth A.; Berg, Erlend; Smith, Sarah; Anderson, Malcolm G.; Holm-Nielsen, Niels (Taylor and Francis, 2018)
Donor-funded infrastructure projects may focus on construction and neglect longer-term sustainability. Engaging local communities has been proposed as way of inducing ongoing maintenance by facilitating coordination and a sense of ownership, but there is little evidence on its effectiveness in practice. We analyse data from inspections of 103 landslide hazard mitigation drains in Saint Lucia several years after construction. We conclude that community participation at the beginning of the project, by accessing local knowledge, is associated with improved construction quality, but appears to have no impact on subsequent maintenance, suggesting that contractual provision for maintenance may be required.